2016
DOI: 10.3389/fpubh.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Knowledge, Attitudes, and Practices in Relation to Mosquitoes and Mosquito-Borne Disease in Western Australia

Abstract: On average, more than 1,000 individuals will acquire a mosquito-borne disease in Western Australia (WA) each year. Knowledge, attitudes, and practices (KAP) in relation to mosquitoes and mosquito-borne disease have not yet been investigated within Australia. A randomized telephone survey of 2,500 households across 12 regions in WA was undertaken between February and May 2014. The aim of the survey was to obtain baseline KAP data surrounding mosquitoes and mosquito-borne diseases in different regions of WA, acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 13 publications
3
28
3
Order By: Relevance
“…Knowledge of mosquito breeding sites among the current study’s respondents also emphasized natural breeding areas like wetlands (67%) and the river foreshore (66%), running counter to Potter et al’s earlier findings [13], who reported that only 33% of state-wide respondents identified wetlands as breeding sites. This points to the local context being a major influence on resident perspectives of factors contributing to mosquito problems, and demonstrates a need to present public health education messages that are tailored to the neighborhood context.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Knowledge of mosquito breeding sites among the current study’s respondents also emphasized natural breeding areas like wetlands (67%) and the river foreshore (66%), running counter to Potter et al’s earlier findings [13], who reported that only 33% of state-wide respondents identified wetlands as breeding sites. This points to the local context being a major influence on resident perspectives of factors contributing to mosquito problems, and demonstrates a need to present public health education messages that are tailored to the neighborhood context.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, three other infections endemic to Western Australia were poorly identified including MVE (13% of respondents), BFV (11% of respondents), and WNV KUN (0% of respondents). These results are similar to those reported by Potter et al [13], who also found that RRV was well recognized among Western Australian respondents in their State-wide survey, but that there is a limited awareness of other endemic infections.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations